Effect of pure curcumin, demethoxycurcumin, and bisdemethoxycurcumin on WT1 gene expression in leukemic cell lines - Anuchapreeda S. (2014)
Purpose: Leukemias are groups of hematological malignancies with high incidence and mortality rates in patients worldwide. There have been shown in many studies that Wilms' tumor1 (WT1) gene were highly expressed in leukemic blast cells. Curcuminoids, major active components of the spice turmeric, are well known for its anticancer. Curcuminoids consist of pure curcumin, demethoxycurcumin, and bisdemethoxycurcumin. In this study, the effect of each curcuminoids'components on WT1 gene expression in leukemic cell lines (K562, HL60, U937, and Molt4) was investigated. Methods: The levels of WT1 mRNA and WT1 protein in leukemic cell lines were assessed by RT-PCR and Western blot analysis, respectively. Results: It was found that the WT1 mRNAs were detected in all 4 types of leukemic cell lines. However, the WT1 protein levels were found only in the cell lines K562 and Molt4. Pure curcumin exhibited a strong inhibitory effect on WT1 mRNA and WT1 protein expression. The treatment of leukemic cell lines with non-cytotoxic doses (5, 10, and 15 μM) of pure curcumin for 2 days reduced the level of WT1 mRNA expression and WT1 protein in a dose-dependent manner. In addition, pure curcumin at 10 μM significantly decreased the level of WT1 mRNA and protein in a time-dependent manner. Conclusion: Pure curcumin, an excellent curcuminoid derivative, decreased WT1 gene expression in both transcriptional and translational levels. Thus, pure curcumin is one of a potential chemotherapeutic agent used for treatment of human leukemia. However, its chemotherapeutic property will need to be studied more in future. © 2007 Springer-Verlag.